PENGARUH MATERIAL TERHADAP DEFORMASI, STRAIN, DAN SAFETY FACTOR PADA BRACKET CALIPER MENGGUNAKAN METODE ELEMEN HINGGA - Ghyferi, Andi Abdullah; Bahatmaka, Aldias; Wibowo, Muhammad Yusuf; Anwar, Ahmad; Ridananda, Ayyub; Vandika, Anggi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The purpose of this study is to analyze the deformation, equivalent elastic strain, and safety factor of a bracket bracket made from two different materials by using the Finite Element Method, specifically aluminum alloy 6061 T6 and cast iron EN GJL 100. The result of this study is that the Aluminum Alloy 6061T6 material has a deformation of 3.57E-04 whereas the Cast iron EN GJL 100 material is 2.75E-04. In the elastic strain equivalent test, the Aluminium alloy 6061 T6 material is 3.00-E07 and in the Cast Iron EN G JL 100 materials is 2.32E-07. In the safety factor test, Cast Iron En G J L 100 material was better than 1.8617 compared to the Alumium Alloys 60 61 T6 materials are 1.5125. This shows that Cast Iron E GJ L 100 materials are better in deformations, eqeuivalent elastic stations, and safety factors in this case.